2017
DOI: 10.17843/rpmesp.2017.343.2276
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes dietéticos del consumo de zinc en menores de cinco años con retardo de crecimiento en comunidades mayas de Guatemala

Abstract: El objetivo del estudio fue identificar elementos del patrón alimentario que influyen en la ingesta y biodisponibilidad de zinc en niños con retardo del crecimiento (RC) entre 1-5 años en comunidades maya de la localidad de Huehuetenango, Guatemala. Estudio descriptivo, transversal aplicado en 138 niños de entre 1-5 años con RC. Se realizó un inventario de disponibilidad alimentaria de fuentes de zinc, se construyó un cuestionario frecuencia de consumo de alimentos, un cuestionario de condiciones de vida, prác… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In a study conducted in the western highlands of Guatemala, tortilla consumption among children was reported to average 5 tortillas per day. Stunting prevalence was 70% and only 60% of mothers carried out adequate nixtamalization practices [36]. Moreover, a recent study in Guatemala reported a negative association between AFB 1 exposure, based on food contamination surveys, and height for age-z scores in children under 5 years of age [37].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in the western highlands of Guatemala, tortilla consumption among children was reported to average 5 tortillas per day. Stunting prevalence was 70% and only 60% of mothers carried out adequate nixtamalization practices [36]. Moreover, a recent study in Guatemala reported a negative association between AFB 1 exposure, based on food contamination surveys, and height for age-z scores in children under 5 years of age [37].…”
Section: Discussionmentioning
confidence: 99%
“…Nixtamalization has been found to reduce some forms of fumonisins in the original maize [32]. However, if fumonisin levels are high in maize, the reduction of fumonisins that occurs through nixtamalization may still result in high levels of contamination in the nixtamalized maize [32,33]. Due to the widespread consumption of tortillas, the ability to detect differences in the quality of maize used to produce tortillas may have been confounded.…”
Section: Discussionmentioning
confidence: 99%